2005
DOI: 10.1126/science.1116865
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Spin Transport in Lateral Ferromagnet/Semiconductor Structures

Abstract: We directly imaged electrical spin injection and accumulation in the gallium arsenide channel of lateral spin-transport devices, which have ferromagnetic source and drain tunnel-barrier contacts. The emission of spins from the source was observed, and a region of spin accumulation was imaged near the ferromagnetic drain contact. Both injected and accumulated spins have the same orientation (antiparallel to the contact magnetization), and we show that the accumulated spin polarization flows away from the drain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
278
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(298 citation statements)
references
References 25 publications
17
278
0
Order By: Relevance
“…In the Datta-Das device, the spinpolarized current which flows in the semiconductor channel, often supposed as a 2-dimensional electron gas (2DEG), is manipulated by electrostatic gate-action, hence providing electrical control of the source-drain current in addition to that provided by the relative alignment of the ferromagnetic contacts. To this end, imaging of the injected spin-polarization from Fe into n-GaAs has been performed in a lateral geometry by Crooker et al 11 and in a cross-sectional geometry by Kotissek et al 12 , whilst Lou et al 13 and Lou et al 14 have demonstrated all-electrical measurements of spin-injection, -transport and -detection in a single Fe/GaAs(001) device. Garlid et al 15 have also used Fe/InGaAs(001) contacts to measure the transverse spin-current generated via the spin-Hall effect.…”
Section: Introductionmentioning
confidence: 99%
“…In the Datta-Das device, the spinpolarized current which flows in the semiconductor channel, often supposed as a 2-dimensional electron gas (2DEG), is manipulated by electrostatic gate-action, hence providing electrical control of the source-drain current in addition to that provided by the relative alignment of the ferromagnetic contacts. To this end, imaging of the injected spin-polarization from Fe into n-GaAs has been performed in a lateral geometry by Crooker et al 11 and in a cross-sectional geometry by Kotissek et al 12 , whilst Lou et al 13 and Lou et al 14 have demonstrated all-electrical measurements of spin-injection, -transport and -detection in a single Fe/GaAs(001) device. Garlid et al 15 have also used Fe/InGaAs(001) contacts to measure the transverse spin-current generated via the spin-Hall effect.…”
Section: Introductionmentioning
confidence: 99%
“…So far, various schemes have been demonstrated to generate and detect spin current in nonmagnetic semiconductors, which include electrical and optical means [2][3][4][5][6][7][8][9][10] . Spin pumping is known as a method to generate a pure spin current without a net flow of charge current in nonmagnetic materials adjacent to a ferromagnetic layer under ferromagnetic resonance (FMR).…”
mentioning
confidence: 99%
“…In recent years, several studies have been performed on epitaxial growth of FM metal thin film on III-V and IV group SCs. [2][3][4][5][6][7] For such type of devices, transition metals and their alloys are of great interest. Among various types of transition metals and alloys, CoFe magnetic alloy is of interest due to its soft magnetic properties.…”
Section: Introductionmentioning
confidence: 99%